PENGARUH FAKTOR MAKRO EKONOMI, FAKTOR LIKUIDITAS DAN FAKTOR EKSTERNAL TERHADAP YIELD OBLIGASI PEMERINTAH INDONESIA - Hary S. Sundoro (Universitas Bunda Mulia, 2018)
This research has been undertaken to delve more deeply about the movement of the governmentbond yield in Indonesia, which is important to be a reference to predict the bond market expectation. Themovement of the government bond yield in Indonesia has been actually caused of a couple of factors, forinstance macroeconomics, liquidity, and external. The data that has been used for this research is fromJanuary 2012 to July 2016. Therefore, according to the result of the unit root test and co-integration,VECM has become a suitable method for accomplishing this research. The outcome of this research,ultimately, has proved that the movement of the government bond yield in Indonesia for all tenor hadbeen fluctuating on account of all variables that contained of macroeconomics, liquidity, and external.The variable that gives the largest contribution for the movement of the government bond yield inIndonesia is the coupon rate itself.Keywords: bond yield, external, macroeconomics, liquidity, VECM